Aislamiento de la proteina transportadora de retinol en suero bovino - Manzanares, D.=700 1 Mella, C.; Colome, H.
(Es, En)
Ilus., 12 ref.
Keywords: PROTEINAS; RETINOL; SUERO DE LECHE; GANADO BOVINO; CUBA